LEÑOS GIMNOSPÉRMICOS DE LA FORMACIÓN MELO (PÉRMICO INFERIOR), URUGUAY. PARTE II. STILOXYLON, POLYSOLENOXYLON y BAGEOPITYS (Ameghiniana, 2014)
Three gymnosperm woods from the Melo Formation (Lower Permian) at arroyo Seco (Rivera Department, Uruguay) are described: Stiloxylon ferrandoi gen. et sp. nov., Polysolenoxylon sp. cf. P. whitei. (Maniero) and Bageopitys sp. These specimens have the pith and the primary and secondary xylem preserved. Stilaxylon ferrandoi shows peculiar features in the initiaJ portion of the secondary wood and in the pith which justify the creation of a new genus and species. The other stems show common characters of aJready known Pa1aeozoicGondwana woods.